An Energy Yield Calculator for Solar Cells Worldwide - Peters, I. M.; Liu, H.; Reindl, Thomas; Buonassisi, T. (2018 IEEE 7th World Conference on Photovoltaic Energy Conversion, WCPEC 2018 - A Joint Conference of 45th IEEE PVSC, 28th PVSEC and 34th EU PVSEC, 2018)
Energy yield is a key metric for photovoltaic technologies. It denotes how much energy a solar cell in an operational environment generates, and it is needed to predict return-on-investment for photovoltaic projects. Determining energy yield, however, is not straightforward as it requires information about the operating conditions that is often not readily available. In this work we introduce a simple method to estimate energy yield for solar cells made from five materials worldwide. We provide a data set based on 2015 meteorological data for each of the five materials CIS, Si, GaAs, CdTe and perovskites. We also show that there is a linear equation allowing to estimating outdoor performance from lab measured efficiency.
CRIS-Team Scopus Importer:2022-06-05
Keywords: band gap; CdTe; CIS; energy yield; GaAs; perovskite; silicon